Zasada pewności prawa w działaniu administracji Unii Europejskiej oraz jako zasada ogólna prawa Unii Europejskiej - Kluczewska-Rupka, Aleksandra (Wydawnictwo Naukowe UAM, 2014)
“Certainty of law” is an expression often present in the justifi cations of decisions of the Constitutional Court and the European Court of Justice. Philosophers consider certainty of law as a major value that law should adhere to. The right to bear the qualifi cation of “certain” is to encourage the need for safety which, according to psychologists, is one of the basic human needs. The principle of legal certainty derives from a broadly defi ned set of principles protecting citizens’ confi dence in the state, the predictability of law, confi dence in the law and the reliability of a legally established order, and is refl ected in the decision delivered by the European Court of Justice of the European Union. Under the rule of law a citizen must be ascertained protection of his predictions or expectations based on the existing legal norms, upon which his confi dence in the state regime is based. Legal certainty is achieved once stability of law is guaranteed and its abolition, or even modifi cations, as some claim, if at all admissible, should be precisely determined by statute. This paper is divided in two parts. The fi rst relates to the compliance with the principle of legal certainty by EU bodies, in which access to information as well as the compliance of the EU administration operations in practice with the principle of legal certainty are analysed. The second part of this paper touches upon the problem of legal certainty – as a general rule, which is frequently referred to in justifi cations of judgments delivered by the Court of Justice of the EU and addressed to Member States. The purpose of this paper is to present adherence to the principle of legal certainty as an intrinsic value which provides citizens with a sense of certainty, stability and predictability. Without a guarantee of these values , the principle of legal certainty remains only a theory.
The principle of legal certainty in the operation of the European Union administration and as a general principle of European Union law
Keywords: certainty of law; administrative law; the Court of Justice of the European Union